Ginger Compress and Warm Lemongrass Compress Therapy for Pain Reduction among Elderly with Rheumatoid Arthritis: A Case Study - Wasis Eko Kurniawan; Jepri Riranto (International Journal of Nursing and Health Services (IJNHS), 2022)
Background: Rheumatoid Arthritis (RA) is a chronic autoimmune inflammatory disorder in which a person's immune system can be compromised and lowered, which destroys the joints and lining of the synovial membrane, especially in the hands, feet, and knees. Objective: The study aimed to examine the effect of ginger compresses, and warm lemongrass compresses on pain reduction among elderly with rheumatoid arthritis. Method: A case study was conducted from January 25, 2022, to January 27, 2022, at the "Dewanata” Elderly Social Service Institution in Cilacap with a patient population of 1 respondent. Pain quality was tested with the effectiveness of ginger compress, and warm lemongrass compresses for 2 days of implementation. Result: The effectiveness of ginger compress and warm lemongrass compresses therapy was different before compressing pain scale 4 and after compressing pain scale 2. Conclusion: the effectiveness of ginger compress and warm lemongrass compresses treatment can reduce pain in rheumatoid arthritis patients. It is hoped that this research in the development of nursing can add to the breadth of knowledge for the process of nursing care with Rheumatoid Arthritis and can be used as a comparison material in carrying out nursing care in cases of Rheumatoid Arthritis in the elderly